Chronic disease, medications and lifestyle: perceptions from a regional Victorian Aboriginal community - Deacon-Crouch M (Pharmacy Practice, 2016)
Background: Poor medication management may contribute to the increased morbidity and mortality of Aboriginal people in Australia. Yet while there is extensive literature about the perceptions of healthcare providers on this issue, there is limited information on the perceptions of Aboriginal people themselves. Objectives: To investigate the perceptions of a group of Aboriginal people attending a Victorian regional Aboriginal Health Service (AHS) with diagnosed medical conditions requiring medications, of their lifestyle, disease management and medication usage. Methods: Data was collected through one to one in depth interviews using a semi-structured ‘yarning’ process. Twenty patients were invited to participate in the study and were interviewed by Aboriginal Health Workers in a culturally appropriate manner. The interviews were recorded and transcribed verbatim. The data were analysed using descriptive statistics. Results: Our results show that the majority of participants perceived that changes in lifestyle factors such as diet, exercise, and smoking cessation would help improve their health. Most patients reported having been counselled on their medicines, and while the majority reported adherence and acknowledgement of the efficacy of their medicines, there was a lack of clarity regarding long term maintenance on regimens. Finally, while the majority reported taking over the counter products, some did not see the need to inform their doctor about this, or chose not to. Conclusion: Chronic illness was perceived as common in families and community. Patients relied mostly on their health care professionals as sources for their drug information. Patients may have benefited from further counselling in the area of complementary and other over the counter medicines, as well as on the necessity of maintenance of regimes for chronic disease management. Finally, lifestyle changes such as dietary improvements and smoking cessation were identified as areas that may assist in improving health outcomes.